2012
DOI: 10.1097/jcp.0b013e31824929b2
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Baclofen for Treatment-Resistant Alcohol Dependence

Abstract: Alcohol dependence is associated with a wide array of physical and psychiatric complications and is a major cause of morbidity and mortality worldwide. Recent randomized trials of baclofen, with a total daily dose 30 mg administered in 3 divided doses, have supported its efficacy in reducing craving and promoting abstinence from alcohol. Individual case studies support a possible increased effect at higher doses for treatment-resistant patients. Here, we report on 4 alcohol-dependent patients resistant to stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…A series of case reports and observational studies indicated that the administration of high doses of baclofen markedly reduced or completely suppressed alcohol intake in patients affected by AUDs [108,109,110,111,112,115,116] as well as the desire to use cocaine in patients affected by CUDs [137]. In France, although baclofen has not been approved for this treatment, an overwhelming number of patients affected by AUDs ask for and receive high doses of baclofen to treat their disorder [175,176].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of case reports and observational studies indicated that the administration of high doses of baclofen markedly reduced or completely suppressed alcohol intake in patients affected by AUDs [108,109,110,111,112,115,116] as well as the desire to use cocaine in patients affected by CUDs [137]. In France, although baclofen has not been approved for this treatment, an overwhelming number of patients affected by AUDs ask for and receive high doses of baclofen to treat their disorder [175,176].…”
Section: Discussionmentioning
confidence: 99%
“…Three case reports showed that the oral administration of baclofen doses ranging between 75 and 125 mg/day was effective in the treatment of AUDs [108,109,110]. Two other case reports found that baclofen administration (from 30 to 400 mg daily) was also effective in reducing or suppressing alcohol consumption in patients affected by AUDs and other psychiatric illnesses in whom previous treatment with other drugs had been unsuccessful [111,112].…”
Section: Baclofen and Sudsmentioning
confidence: 99%
“…dose of 125 mg/d either alone, or in combination with acamprosate or naltrexone, was published [21]. In two cases they found prolonged abstinence even after the dosage was reduced to 50 mg/d.…”
Section: Clinical and Experimental Pharmacologymentioning
confidence: 99%
“…The preliminary anecdotal 'auto-case' dose reported by a physician to suppress his craving was however as high as 270 mg/day with gradual dose escalation (Ameisen, 2005). Although there are no studies on safety of high dose Baclofen with concurrent alcohol use, it is often prescribed in clinical practice, especially for patients who are unresponsive to approved treatments (Pastor et al, 2012;Rigal et al, 2012). The lack of proper recommendations regarding the dosage has important implications for safety in clinical management.…”
Section: Introductionmentioning
confidence: 98%